A comparison study of complications and initial follow-up costs of transcutaneous and percutaneous bone conduction devices. Issue 8 (19th June 2017) - Godbehere, J; Carr, S D; Moraleda, J; Edwards, P; Ray, J
Abstract: Background: The percutaneous osseointegrated bone conduction device can be associated with more soft tissue complications when compared to the magnetic transcutaneous osseointegrated bone conduction device. This study aimed to determine whether fewer soft tissue complications may result in the transcutaneous osseointegrated bone conduction device being a lower cost option in hearing rehabilitation. Methods: This retrospective case note review included adult patients who underwent implantation with the transcutaneous Cochlear Attract ( n = 22) or percutaneous Cochlear DermaLock ( n = 25) bone-anchored hearing aids between September 2013 and December 2014. The number of post-operative clinic appointments, complications and treatments undertaken, and calculated cost average, were compared between the two groups. Results: Although the transcutaneous device was slightly more expensive than the percutaneous device, the percutaneous device was associated with a greater number of soft tissue complications and, as a result, the percutaneous device had significantly higher follow-up costs in the first six months following surgery. Conclusion: The transcutaneous osseointegrated bone conduction device may represent a more cost-effective method of hearing rehabilitation compared to the percutaneous osseointegrated bone conduction device.